Score GPS-GF para predecir mortalidad a 30 días en pacientes con ICTUS isquémico cardioembólico por fibrilación auricular - Timaná Cabrera, Renzo Martín (2019)
The cardioembolic ischemic stroke due to atrial fibrillation (AF) has a mortality as high as 22-27% at 30 days post-onset. The GPS-GF score is the first risk score to predict mortality, performed specifically for patients with stroke caused by AF. OBJECTIVE: To assess the validity of the GPS-GF score to predict 30-day mortality in patients with cardioembolic ICTUS due to atrial fibrillation, hospitalized at the Hospital Regional Docente de Trujillo (HRDT). MATERIALS AND METHODS: A retrospective analytical study conducted at the HRDT, with a sample of 82 medical records of patients hospitalized in the Neurology department during the 2012-2018 period that met inclusion criteria, to which the GPS-GF score was applied. ROC curve was constructed to see discriminative capacity and better cut point. RESULTS: The area under the curve for GPS-GF score was 0.946, with p = 0.000, CI = 95% (0.899-0.993), being statistically significant. Cut-off point 4 was the best for prediction of 30-day mortality (Sensitivity: 81.81%, Specificity: 93.33%, PPV: 81.81% and NPV: 93.33%). CONCLUSION: The GPS-GF score is valid for predicting 30-day mortality in patients with cardioembolic ICTUS due to atrial fibrillation of the HRDT.